THE EFECT OF IMMUNOMODULATOR BY EXTRACT ETHANOL OF HERBA BINARA (ARTEMISIA VULGARIS L.) TOWARD THE RESPONSE OF DELAYED-TYPE HYPERSENSITIVITY IN RAT MALE - Romauli Anna Teresia Marbun; Novidawati Situmorang; Sri Wahyuni (Jurnal Penelitian Farmasi & Herbal, 2018)
Immunomodulator is a compound that can increaase the imuno system. One of the plants that have immunomodulator’s activity is Herba Binara (Artemisia vulgaris L.). the purpose of this research was to test the effect of immunomodulator by extract of herba binara ethanol on rat male. The activity of immunomodulator was determined by using digital pletysmometer by measuring the differences between the last leg swelling’s volume and the first leg swelling’s volume. The treatment group were divided into 5 groups. Each group consistof 5 rats CMC-Na 0,5% (negative control), Imboost 32,5 mg/kgBW (positive control), dose of EEHB 50, 100, 200 mg/kgBW, and bacteria E.coli as antigen. The results slowed that distribution of EEHB dose 200 mg/kgBW can give the effect of immunostimulant by swelling enthancement compared by CMC-Na 0,5 %. EEHB 200 mg/kgBW that have activity comparable with Imboost 32,5 mg/kgBW. Thus, it is concluded that of herba binara extract has immunomodulator effects on delayed-type hypersensitivity response of rat male.